Pro-Duterte blogger quits DFA contract - Pazzibugan, Dona Z. (2017)
A pro-Duterte blogger has backed out of his contract as consultant to the Department of Foreign Affairs (DFA), less than a week after being called to Senate hearing on fake news.
Keywords: Nieto, Rey Joseph; Philippines. Department of Foreign Affairs -- Officials and employees